2015
DOI: 10.2134/cftm2015.0150
|View full text |Cite
|
Sign up to set email alerts
|

Herbicides Applied at or Shortly after Seeding Are Effective for Weed Control in Seedling Buffalograss

Abstract: Herbicides applied shortly after seeding of buffalograss [Buchloe dactyloides (Nutt.) Engelm.] can help reduce weed pressure and maximize establishment of buffalograss. This study evaluated 12 relatively recently developed herbicides for turf safety and weed control when applied at seeding or 0 or 2 weeks after emergence (WAE) of ‘Bowie’ or ‘Sundancer’ buffalograss. Primary weed species on the site were common purslane (Portulaca oleracea L.), redroot pigweed (Amaranthus retroflexus L.), and/or yellow foxtail … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
8
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 7 publications
0
8
0
Order By: Relevance
“…In our study, established Bowie buffalograss was most tolerant to carfentrazone + quinclorac, halosulfuron, indaziflam, quinclorac, quinclorac + MCCP + dicamba, simazine, sulfosulfuron, or thiencarbazone + iodosulfuron + dicamba. This research, combined with our previous study of herbicide use on newly seeded buffalograss (Li et al, 2015), show that a wide range of herbicides can be safely applied to buffalograss at many different growth stages.…”
mentioning
confidence: 56%
“…In our study, established Bowie buffalograss was most tolerant to carfentrazone + quinclorac, halosulfuron, indaziflam, quinclorac, quinclorac + MCCP + dicamba, simazine, sulfosulfuron, or thiencarbazone + iodosulfuron + dicamba. This research, combined with our previous study of herbicide use on newly seeded buffalograss (Li et al, 2015), show that a wide range of herbicides can be safely applied to buffalograss at many different growth stages.…”
mentioning
confidence: 56%
“…Mesotrione likely increased percent turf cover compared to the control because weeds were not able to infest the plot (Li, Sousek, & Reicher, 2015). Weed suppression at the 0.088 kg a.i.…”
Section: Resultsmentioning
confidence: 99%
“…The absence of mesotrione resulted in lower percent turf cover due to higher weed infestation by large crabgrass (Digitaria sanguinalis L.), dandelion (Taraxacum officinale L.), and yellow foxtail (Seteria pumila L.). Mesotrione likely increased percent turf cover compared to the control because weeds were not able to infest the plot (Li, Sousek, & Reicher, 2015). Weed suppression at the 0.088 kg a.i.…”
Section: Experiments 1: Mesotrione Rate Effects In Hydroseeding Slurrymentioning
confidence: 98%
“…Despite its resilience in low‐input management, buffalograss is still susceptible to encroachment by weeds that can reduce aesthetics and traffic tolerance (Brosnan et al., 2014). Previous research has demonstrated safety of seedling and established buffalograss to spring and summer applications of pre‐emergence herbicides (Dotray & McKenney, 1996; Fry et al., 1997) and postemergence herbicides (Fry et al., 1997; Goss et al., 2006; Li et al., 2015; Li et al., 2017; Li et al., 2018; Van Dyke & Johnson, 2009). Additional research demonstrated the safety of postemergence herbicide applications on buffalograss entering winter dormancy (Braun et al., 2018).…”
Section: Herbicide Use In Buffalograssmentioning
confidence: 99%